Organizational trust and organizational silence: the factors Predicting organizational commitment. - ., Helmiati; Rasyid Abdillah, Muhammad; Anita, Rizqa; Nofianti, Leny; Balkish Zakaria, Nor (International Journal of Engineering and Technology, 2018)
This study examines the impact of organizational trust on organizational commitment through organizational silence and job satisfaction among academics in Indonesia. A total of 309 respondents from private sector higher education institutions participated in this research. The result from partial least square-structural equation modeling analysis reveal that organizational trust has a negative effect on organizational silence, and organizational silence has a negative effect on job satisfaction and organizational commitment. In other words, individuals with low trust tend to do silence at the organization, not satisfied with the job and low commitment. In addition, the result also suggests the effect of organizational trust on organizational commitment is indirectly influenced by organizational silence and job satisfaction.Â